Cellular Automata Markov Chain Application For Prediction Of Land Cover Changes In The Wae Batu Gantung Watershed, Ambon City, Indonesia: Aplikasi Cellular Automata Markov Chain Untuk Prediksi Perubahan Tutupan Lahan DAS Wae Batu Gantung Kota Ambon Indonesia - Rakuasa, Heinrich; Philia Christi Latue (Journal of Multidisciplinary Science, 2023)
The development of built-up land over the last 15 years in Ambon City has affected changes in land cover in the Wae Batugantung watershed. This is due to increasing population growth, and the increasing need for residential land. Changes in land cover in the Wae Batu Gantung watershed have an impact on land degradation, water pollution, flooding, and erosion, which will increase in the future. This study aims to analyze land cover changes in the Wae Batu Gantung watershed in 2012, 2017, 2022, and predict land cover in 2027, and 2031. The Cellular Automata Markov Chain method was used in this study to predict the spatial dynamics of land cover change. The results of the study show that from 2012, 2017, 2022, and predictions for 2027, and 2031 residential land, and open land in the Wae Batutangan watershed continue to expand, in contrast to non-agricultural land cover, and agricultural land which is decreasing. The results of this study are expected to be input into policy making related to spatial utilization in the Wae Batugantung Watershed in the future.